Unity concept from Islamic perspective and the reality of unity in Malaysia - Md. Yassin, Sulaiman; Dahalan, Dzuhailmi (International Institute for Science, Technology & Education, 2012)
Unity is a drive towards social stability of a country. Any society and the nation as a whole might be ruined, if the issue of unity cannot be solved intelligently and with wisdom. Unity as a concept has always been misunderstood among members of certain communities, therefore this issue not only persists in the context of a plural society, but also abide in a community of homogeneous religion or race. The dream for unity must be based on clear evidence and not merely hypothetical. The glory of Islam’s past civilization clearly demonstrates the bond of brotherhood in a multicultural society that is sustained for such long periods of time. Such glory is a manifestation of the great messenger’s determination, the Prophet Muhammad and his companions who advocated righteousness and forbid evil based on the guidance from God. The concept of brotherhood and harmony commanded by Allah is well understood by them. The question is whether that methodology is understood by today’s society, specifically among Muslim leaders. Therefore, this paper briefly explores the concept of unity in Islam based on the guidance of Quran and Hadith, and the views of academics who debate this issue. The paper also initiates a brief discussion on some selected findings that relate to the situation of unity and national integration in Malaysia.